The intricate role of miR-155 in carcinogenesis: potential implications for esophageal cancer research. (23rd January 2019) - Nariman-Saleh-Fam, Ziba; Saadatian, Zahra; Daraei, Abdolreza; Mansoori, Yaser; Bastami, Milad; Tavakkoli-Bazzaz, Javad
MiRNAs have immerged as essential modulators of key cellular procuresses involved in post-transcriptional regulation of the human transcriptome. They are essential components of complex regulatory networks that modulate most important physiological functions of cells. MicroRNA-155 (miR-155) is a multifaceted regulator of cell proliferation, cell cycle, development, immunity and inflammation that plays pivotal, and sometimes contradictory, roles in numerous cancers including esophageal cancer. Here, we review the intricate role of miR-155 in cancer by exemplifying carcinogenesis of various tumors, focusing on recent findings that may provide a link between miR-155 and esophageal cancer-related pathways.